2006
DOI: 10.1128/iai.00768-06
|View full text |Cite
|
Sign up to set email alerts
|

The Cryptococcal Enzyme Inositol Phosphosphingolipid-Phospholipase C Confers Resistance to the Antifungal Effects of Macrophages and Promotes Fungal Dissemination to the Central Nervous System

Abstract: In recent years, sphingolipids have emerged as critical molecules in the regulation of microbial pathogenesis. In fungi, the synthesis of complex sphingolipids is important for the regulation of pathogenicity, but the role of sphingolipid degradation in fungal virulence is not known. Here, we isolated and characterized the inositol phosphosphingolipid-phospholipase C1 (ISC1) gene from the fungal pathogen Cryptococcus neoformans and showed that it encodes an enzyme that metabolizes fungal inositol sphingolipids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
110
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 48 publications
11
110
0
Order By: Relevance
“…Isc1p deficiency increased H 2 O 2 -and aginginduced intracellular oxidation, protein carbonylation, and lipid peroxidation. In agreement, Isc1p protects the fungus Cryptococcus neoformans from the oxidative stress environment of macrophages (Shea et al, 2006). Interestingly, isc1⌬ cells accumulate IPC and M(IP) 2 C (Sawai et al, 2000), and other yeast mutants showed an inverse correlation between oxidative stress resistance or chronological lifespan and M(IP) 2 C levels (Aerts et al, 2006).…”
Section: Discussionmentioning
confidence: 49%
“…Isc1p deficiency increased H 2 O 2 -and aginginduced intracellular oxidation, protein carbonylation, and lipid peroxidation. In agreement, Isc1p protects the fungus Cryptococcus neoformans from the oxidative stress environment of macrophages (Shea et al, 2006). Interestingly, isc1⌬ cells accumulate IPC and M(IP) 2 C (Sawai et al, 2000), and other yeast mutants showed an inverse correlation between oxidative stress resistance or chronological lifespan and M(IP) 2 C levels (Aerts et al, 2006).…”
Section: Discussionmentioning
confidence: 49%
“…21 The intracellular sequestra-tion of viable cryptococci within AMs contributes to propagation of infection during the pre-effector phase of the host response [approximately 0 -14 days post-infection (dpi)]. [25][26][27][28][29] Yet, AMs also protect against deleterious and ineffective inflammation before the onset of adaptive immunity. 30 Previous studies 31,32 identified macrophage accumulation in the lungs of cryptococcal-infected mice during the effector phase (approximately 14 -28 dpi) of the host response.…”
mentioning
confidence: 99%
“…In contrast, the deletion of ISC1, coding for an inositol phosphosphingolipid-phospholipase C, enhances the sensitivity of yeast to oxidative stresses and to acidic environments. In a mouse model of cryoptococcosis in immunocompetent mice, ΔISC1 mutant are less virulent and more sensitive to phagolysosome stress inside the macrophage, showing the importance of IPC structures in fungal pathobiology [80]. These data show that both fungal types of SPL, GlcCer and IPC, are required for the resistance to host environment.…”
Section: Role Of Spls In Host-pathogen Interaction and Pathogenesismentioning
confidence: 69%